2015
DOI: 10.1016/j.jscs.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound agitated phytofabrication of palladium nanoparticles using Andean blackberry leaf and its photocatalytic activity

Abstract: In this report, ultrasonication and Andean blackberry leaf extract are employed for the fabrication of palladium nanoparticles (PdNPs); and further evaluated its photocatalytic activity against methylene blue (MB). The as-synthesized PdNPs were characterized using UV-visible spectroscopy, transmission electron microscopy (TEM), Dynamic light scattering (DLS) and X-ray diffraction (XRD). TEM analysis demonstrated the formation of decahedron shape PdNPs with a diameter of 55-60 nm and XRD confirmed its crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Synthesis, characterization and application of palladium nanoparticles as photocatalytic agent have been reported [14, 15]. The degradation of phenol red by palladium nanoparticles has been investigated.…”
Section: Reviewmentioning
confidence: 99%
“…Synthesis, characterization and application of palladium nanoparticles as photocatalytic agent have been reported [14, 15]. The degradation of phenol red by palladium nanoparticles has been investigated.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, Pd NPs were fabricated via ultrasonication of Andean blackberry leaf extract and were used for photocatalytic degradation of methylene blue. 23 Rao et al 24 reported enhanced photocatalytic degradation of bisphenol A by Pd/PdO/β-Bi 2 O 3 microspheres and M. A. Khan's research team 25 used guar gum as stabilizer to synthesize Pd NPs and applied the Pd NPs as catalysts for the degradation of azo dyes. However, these methods are complicated and difficult for synthesizing Pd NPs and some require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…and eucalyptus [7,8,13,14]. Other parts of plants have also been used such as Piper longum and Crataegus douglasii fruit extract, coffee powder extract, Nephelium lappaceum, orange peel extract, oil of Plukenetia volubilis L., Chrysanthemum morifolium Ramat extract, Medicago sativa and Sterculia foetida seed exudate, sorghum bran extract and Cinnamon zeylanicum bark extract [6,7,10,11,[15][16][17][18][19][20][21].…”
mentioning
confidence: 99%